Pengaruh Model Pembelajaran Project-Based Learning Berbantuan Scrapbook Terhadap Hasil Belajar Siswa pada Materi Sistem Ekskresi Manusia - Triwulandari Saleh; Debby J. J. Rayer; Nonny Manampiring (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to find out whether Project Based Learning using scrapbooks has an effect on improving student learning outcomes in human excretory system material at SMA Negeri 1 Motoling. This study was conducted using an experimental method with a pre-test post-test control group design research design. The sample in this study consisted of two classes, namely class XI 5 as an experimental class with 20 students and class XI 7 as a control class with 20 students. The results of the research in the experimental class found that the maximum post-test score was 90, and the minimum score was 65 with an average number of 77. In the control class, the maximum post-test score was 85 and the minimum score was 20 with an average of 46.26. Thus, it can be concluded that there is a significant influence of the use of the project-based learning model using scrapbooks on student learning outcomes at SMA Negeri 1 Motoling on the material of the human excretory system.